POTENCY OF EXTRACT AND FRACTION OF SPONGE Lamellodysidea herbacea OBTAINED FROM MANADO TUA ISLAND AGAINST Staphylococcus aureus AND Escherichia coli - Angellia Grace Yetto; Defny Wewengkang; Elly Suoth (UNIVERSITAS SAM RATULANGI, 2022)
Sponges has many kind of secondary metabolites and has potential as important clues in drug development. This study aims to determined the potential level of Sponge Lamellodysidea herbacea obtained from Manado Tua Island waters as an antibacterial agent against Staphylococcus aureus and Escherichia coli bacteria. The samples were extracted using maceration method with ethanol solvent and fractionated with n-hexane, chloroform and methanol as solvents. Antibacterial activity was tested using agar diffusion method (Disc Diffusion Kirby and Bauer). The result showed that all of the fractions and crude extract had antibacterial activities against Staphylococcus aureus and Escherichia coli. The best antibacterial activity was found in the n-hexane fraction against Escherichia coli bacteria with an inhibitory power 11.05 mm and the chloroform fraction against Escherichia coli with an inhibitory power 21.99 mm.